Difundindo arquivos: uma experiência em arquivos escolares - ALMEIDA, Rosiane da Silva (2023)
The objective of this work is to present the Project Spreading Archives: Revealing Memories and Narrating Stories that is configured as an extension practice that enables the diffusion of collections from institutions in Pará. Methodologically, the project was guided by bibliographic and documentary research, on site visits to selected collections, preparation of scripts and video editing, resulting in the development of audiovisual products available on social medias. This study highlights the experience in the archive of the State School of Elementary and High School Dr. Freitas. It is concluded that the practice of dissemination is an important tool for accessing information and that school files represent a relevant source for educational research, for the preservation of the memory of the school community and for the enforcement of rights.